Biosorption of Methylene Orange Dye using Langsat Shell by Batch Method - Kurniawati, Desy; Lestari, Intan; Tarmizi, Fadhilah; Pernadi, Niza Lian; Iqbal, Anwar (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Liquid waste is a major problem in the textile industry environment that has the most widespread influence because physical and aquatic characteristics can have a negative impact on waters. Most of the liquid waste produced by batik comes from the dyeing process and environmental pollution. If it is disposed of directly into the environment without prior processing, the environment has a limited ability to degrade dyestuffs. One alternative method to remove the dye in water contaminated with methyl orange is biosorption using a cheap and easily available biosorbent, such as a langsat shell. This study used a batch method with variations in pH, solution concentration, particle size, stirring speed, and contact time. The results of each variation carried out obtained the optimum conditions for the absorption of Methyl Orange, namely at: pH 4, concentration 150 mg/L, and particle size 150 Î¼m. The adsorption isotherm study was carried out, the Langmuir equation yielded a regression coefficient value that was close to one (R2 = 0.9964) so that it could be said to be better with a maximum absorption capacity of 3.1164 mg/g